Chemoinformatic characterization of activity and selectivity switches of antiprotozoal compounds. (March 2014) - Aguayo-Ortiz, Rodrigo; Pérez-Villanueva, Jaime; Hernández-Campos, Alicia; Castillo, Rafael; Meurice, Nathalie; Medina-Franco, José L
Background: Benzimidazole derivatives are promising compounds for the treatment of parasitic infections. The structure–activity relationships of 91 benzimidazoles with activity against Trichomonas vaginalis and Giardia intestinalis were analyzed using a novel activity landscape modeling approach.Results: We identified two prominent cases of 'activity switches' and 'selectivity switches' where two R group substitutions in the benzimidazole scaffold completely invert the activity and selectivity pattern for T. vaginalis and G. intestinalis .Conclusion: A chemoinformatic methodology was used to rapidly identify discrete structural changes around the central scaffold that are associated with large changes in biological activity for each parasite. The structure–activity relationships for the benzimidazole derivatives is smooth for both protozoan with few but markedly important activity cliffs.